Zakat Sebagai Upaya Peningkatan Kesejahteraan Dalam Perspektif Surah At-Taubah Ayat 60 - Nur Hasan; Muhammad Bintang; Ahmad saputra (Penerbit Hellow Pustaka, 2024)
This research is motivated by the most common problem in Indonesia, namely poverty, poverty occurs due to unequal income and lack of effectiveness in the field of management and fund management. The purpose of formal zakat management is to increase the effectiveness and efficiency of zakat administration and increase the benefits generated from zakat to improve community welfare and poverty prevention. Analysis of Qur'anic verses, search of related literature, and data collection from respondents representing various layers of Islamic society are qualitative research methods. Zakat can be given to eight groups, according to surah At-Taubah verse 60. The groups entitled to receive zakat include amil (people who take care of zakat), muallaf (people who have just converted to Islam and need help to adjust to their new circumstances), slave (newly freed slaves), Gharim (people who owe money for lawful needs but are unable to pay it), and Fisabilillah (people who fight in the way of Allah). Ibnu sabil are those who run out of money to travel for purposes such as da'wah and others.